Optimalisasi Kompetensi Pedagogik Calon Guru PAI Melalui Implementasi Flipped Classroom Berbasis Moodle pada Microteaching - Fatmawati Nur Hasanah (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
Some students in Islamic Religious Education (PAI) study programs students still have low pedagogical competence. It is deemed necessary to increase the pedagogical competence of prospective PAI teachers, one of which is by implementing a Moodle-based flipped classroom on microteaching. Specifically, this research focuses on 1) how is the implementation of the Moodle-based flipped classroom on microteaching in improving the pedagogical competence of prospective PAI teachers, 2) Describing the effect of the implementation of the Moodle-based flipped classroom on the pedagogical competence of prospective PAI teachers, and 3) Knowing student responses to the implementation of the flipped classroom Moodle-based on microteaching. The results showed that: 1) Implementation of Moodle-based flipped classroom on microteaching at UIN K.H. Abdurrahman Wahid Pekalongan is carried out with e-learning on the http://learning.iainpekalongan.ac.id/ page, 2) Based on the results of the t-test (paired sample test) that the value of t count = [-44,338] or 44,338 while the value of t table = 2.028 so that 44.338 > 2.028, and a Significance value (2-tailed) of 0.000 so that 0.000 <0.05, it can be concluded that there is an effect of the implementation of moodle-based flipped classrooms in microteaching courses on the pedagogical competence of prospective teachers, 3) Student responses to Microteaching courses are included in the category very positive, the Moodle LMS is included in the positive category, and the flipped classroom is included in the positive category.